1997
DOI: 10.3354/meps159097
|View full text |Cite
|
Sign up to set email alerts
|

Coastal and deep-sea benthic diversities compared

Abstract: Most generalisations about marine benthic diversity (species richness) are derived from few studies, few samples and low specles numbers. It is questionable whether the data on whlch most parad~gms, espec~ally about the deep sea, are based truly represent general patterns of marine diversity. Available information from deep-sea studies are summarised and compared with some extensive data sets from the shallow coasts of Norway and Australia. We show that species richness per unit area is as hlgh, if not higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 21 publications
0
76
0
2
Order By: Relevance
“…Gray et al (1997) also concluded that evenness in the deep sea is higher than in shallower coastal environments. Extensive polychaete data sets from the recent ANDEEP expeditions to the Weddell Sea shelf and slope and Southern Ocean abyssal plain are also consistent with observations of high evenness at abyssal sites relative to Antarctic shelf sites (Schüller & Ebbe 2007, Schüller et al 2009).…”
Section: Antarctic Benthic Diversity In a Regional And Global Contextmentioning
confidence: 99%
“…Gray et al (1997) also concluded that evenness in the deep sea is higher than in shallower coastal environments. Extensive polychaete data sets from the recent ANDEEP expeditions to the Weddell Sea shelf and slope and Southern Ocean abyssal plain are also consistent with observations of high evenness at abyssal sites relative to Antarctic shelf sites (Schüller & Ebbe 2007, Schüller et al 2009).…”
Section: Antarctic Benthic Diversity In a Regional And Global Contextmentioning
confidence: 99%
“…Since then, the question of whether the deep sea is (hyper) diverse (Gray, 1994(Gray, , 2002Gray et al, 1997;Lambshead and Boucher, 2003) and what mechanisms maintain such high diversity (Grassle and Sanders, 1973;Grassle, 1989;Gage and Tyler, 1991;Etter and Grassle, 1992;Lambshead, 1993;Rogers, 2000;Levin et al, 2001;Snelgrove and Smith, 2002;Rex et al, 2005b) have been constantly discussed and remain controversial (May, 1994). According to Gage and Tyler (1991), seasonal food input is one of the factors that is a source of temporal patchiness and regulates species coexistence in the deep sea.…”
Section: Large-scale Diversity Trendsmentioning
confidence: 99%
“…(4) Today's challenge to many researchers of the marine environment is to find answers to the questions dealing with diversity clines along depth gradients (Gray et al 1997) or latitudinal gradients (Arntz & Gallardo 1994). The general opinion is that, e.g., the deep sea and Antarctica contain highly diverse communities, though this view is far from straightforward and certainly requires confirmation from further sampling.…”
Section: Introductionmentioning
confidence: 99%